Filter's retraction hook capture technique of pull-assisted method for endovascular retrieval of conical inferior vena cava filters whose hook attached to the wall - Tian, Xuan; Liu, Jianlong; Zheng, Han; Li, Jinyong; Liu, Xiao; Zhou, Mi; Qu, Chengjia; Hua, Run; Tian, Chenyang (Frontiers in Surgery, 2026)
BackgroundPermanent placement of venous filters can lead to numerous complications. When the risk of pulmonary embolism (PE) decreases, it is recommended to retrieve the filter. Inferior vena cava (IVC) filter retrieval is primarily performed intraluminally; however, the retrieval hook for conical filters may penetrate the venous wall, causing failure of the intraluminal retrieval: some filters are retrieved using the Loop-snare technique or its modified version, some are retrieved through open surgery, which causes more damage, and some are left permanently in place. For these patients, a filter's retraction hook capture technique of pull-assisted method can be used effectively to retrieve the filter. This study introduces a surgical method using the novel technique for the intraluminal removal of conical IVC filters whose retraction hook attached to the wall, along with the outcomes and a 3-month follow-up.MethodsFrom January 2021 to December 2024, patients with conical filters whose retraction hook attached to the wall were enrolled consecutively. Various advanced filter retrieval techniques were initially used to remove the filters, and those that were unsuccessful were subsequently treated with the new technology for filter retrieval. The patients were divided into a successful group and a failure group based on whether the filter retrieval was successful. Retrospective comparative analysis was performed to evaluate patient characteristics, filter retrieval rate, inclination, penetration distance, and IVC imaging.ResultsA total of 44 patients underwent filter retrieval using filter's retraction hook capture technique of pull-assisted method. Among these patients, 37 cases (84.1%) were successful in filter retrieval (successful group), with the penetration distance of cranial anchor vertex of 3.2 (2.5, 4.3) mm, and 12 (32.4%) filters were deformed. The other seven cases (failure group) were unsuccessful, with a penetration distance of cranial anchor vertex of 5.0 (4.3, 5.0) mm, and 6 (85.7%) filters were deformed. There was a statistically significant difference between the two groups (P < 0.05). One case (2.3%) had IVC injury, one case (2.3%) experienced filter fracture, and no symptomatic PE occurred. Logistic regression analysis was performed to identify factors that might affect filter retrieval, with an odds ratio (OR) of 0.069 (0.006, 0.828), suggesting a statistical difference between filter deformation and successful retrieval. Logistic regression analysis was also performed to determine factors influencing filter inclination, with the results indicating a statistically significant difference in the penetration distance and the transverse diameter of the IVC [OR = 0.667 (0.465, 0.958) and OR = 0.843 (0.712, 0.998), respectively], indicating a statistically significant difference in the penetration distance and the transverse diameter of the IVC, and affecting severe filter inclination.ConclusionFilter's retraction hook capture technique of pull-assisted method is effective in removing conical filters whose hook attached to the wall, with no symptomatic PE occurring. This method can be considered as a new adjuvant technique for filter retrieval.